MULTICOLOR FLOW CYTOMETRY AS A DIAGNOSTIC TOOL IN MYELODYSPLASTIC SYNDROMES - Yu. O. Davydova; I. V. Galtseva; A. V. Kokhno; Е. N. Parovichnikova (Онкогематология, 2018)
Myelodysplastic syndromes (MDS) are heterogeneous group of clonal hematological neoplasms characterized by cytopenias, sighs of dysplasia and high risk of transformation in acute myeloid leukemia. Diagnostics of MDS requires a comprehensive approach, but even when performing cytological, cytogenetic, molecular and histological studies, it is not always possible to establish a diagnosis. Multicolor flow cytometry (MFC) is a high-tech method, increasingly used in the diagnosis of various hematologic diseases. Over the last years, MFC is standardized for assessing of dysplasia in all cell compartments of the bone marrow. Many research groups have demonstrated high sensitivity and specificity of this diagnostic approach, which indicates the necessity of integration of flow cytometric study into diagnostic protocols of MDS.